A video intervention reduces racial bias in a representative sample of US adults: A brain as predictor study - Yilong Wang; Paul J. Zak (PLoS ONE, 2026)
Biased attitudes and behaviors towards racial minorities in the US are pervasive, enduring, and detrimental. We tested whether a video illustrating the negative effects of racial bias towards African-Americans would influence short-term and medium-term attitudes and behaviors towards this group. In Experiment 1, a high-impact video was identified by measuring neurologic Immersion in the laboratory (N = 62). Experiment 2 then recruited a representative sample of US adults (N = 1097) to assess the video’s impact on attitudes and behaviors towards African-Americans relative to participants who watched a neutral control video. A two-week follow up study was also done to determine if effects of the treatment video persisted. At baseline, young participants, men, and Republicans, had the statistically highest attitudinal bias towards African-Americans. We found that the treatment video improved average self-reported attitudes towards Black Americans by 11% (p < 0.001; Cohen’s d = 0.26) and generosity in a hypothetical money sharing task with a Black male by 104% (p = 0.016; Cohen’s d = 0.22) compared to controls. These effects were primarily driven by a reduction in attitudinal biases by participants with the highest basal bias. We also showed that these effects were mediated by an increase in positive affect due to the video. Both treatment effects persisted after the washout period indicating that high neurologic Immersion videos may be an effective way to reduce out-group biases at scale.